Chronology of the Klip River Affair of 1847 - Leśniewski, Michał (Werkwinkel, 2014)
The aim of the present article is the reconstruction of the chronology of the klip River affair of 1847. Reading primary sources and literature for the natal history in the 1840s I realized that the chronology of the klip River affair is incomplete and incorrect, a d that this affects the analyses of this affair and the whole situation of natal colony at that time. Therefore the decision to reconstruct the chronology of this affair as much as possible and put it straight, in hope that it will be helpful for further studies of kwaZulunatal history during 1840s and 1850s.